2010 IEEE International Symposium on Information Theory 2010
DOI: 10.1109/isit.2010.5513705
|View full text |Cite
|
Sign up to set email alerts
|

A fast Generalized Minimum Distance decoder for Reed-Solomon codes based on the extended Euclidean algorithm

Abstract: This paper presents a method to determine a set of basis polynomials from the extended Euclidean algorithm that allows Generalized Minimum Distance decoding of ReedSolomon codes with a complexity of O(nd).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…without increasing complexity. A similar result was achieved in [4], [5] for the Euclidean algorithm and in [6] using Newton interpolation. Up to our knowledge, there is no such modification of Guruswami-Sudan (GS) [7] list decoding -which can be considered as state of the art in algebraic decoding -so far.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…without increasing complexity. A similar result was achieved in [4], [5] for the Euclidean algorithm and in [6] using Newton interpolation. Up to our knowledge, there is no such modification of Guruswami-Sudan (GS) [7] list decoding -which can be considered as state of the art in algebraic decoding -so far.…”
Section: Introductionsupporting
confidence: 78%
“…,h n−1 ),h 0 ≥ · · · ≥h n−1 , by averaging over 10 4 random unreliability vectors. For each variant of P (τ ) (exact, Hoeffding approximation, ε 0 (τ ) approximation), we calculateτ := τ ⋆ forh according to (4). We useτ for every received vector, which means that the simulation is in fact non-adaptive, using the optimal erasing strategy for the average unreliability vector.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…which has a form similar to the key equation (5). This implies that the EEA can be used for solving (5). Hence by setting…”
Section: A Decoding Up To D−1mentioning
confidence: 99%
“…In [5] it was shown that c (j+1) , the number of coefficients of q (j+1) (x) that can be determined from the syndrome, is given by…”
Section: B From Classical Decoding To Gmd Extensionmentioning
confidence: 99%
See 1 more Smart Citation